HUBUNGAN AKTIFITAS FISIK DENGAN TEKANAN DARAH PADA LANSIA DI DUSUN MIRI DESA SRIHARJO IMOGIRI BANTUL YOGYAKARTA - Mila, Marina; Anida, Anida; Ernawati, Yuli (Jurnal Kesehatan Masyarakat, 2017)
ABSTRACT HIGH BLOOD PRESSURE has become a disease of concern in many countries in the world, the prevalence of hypertension in Indonesia was 26.5 percent. Special Region of Yogyakarta (DIY) belong to a group with the number of hypertension patients is quite high at 25% . Bantul Yogyakarta Province which includes the districts with the number of people with hypertension is high at 26.12%. Based on data from the District Health Office in Bantul in 2015, cases of hypertension highest in Puskesmas Imogiri II with a number of 5260 cases, data hypertension highest in the village Sriharjo with a number of 562 cases, and Hamlet highest Dusun Miri with the number of cases of hypertension as many as 88 cases. Objective To determine the relationship of physical activity on blood pressure in elderly in the village of Miri, Sriharjo, Imogiri, Bantul, Yogyakarta. This study used a survey of observational with cross sectional approach, as well as data analysis using the Fisher exact test. fisher exact test results between physical activity levels of blood pressure in the elderly in the village of Miri, Sriharjo, Imogiri, Bantul, Yogyakarta, known fisher exact significance of test results obtained Pearson chi-square value amounted to 31,080, with 0,000 p value